Development of a novel prognostic score for 1-year survival in immunotherapy-treated patients with unresectable HCC: the ALIVE-IO score - Pantzios, Spyridon; Sidiropoulos, Orestis; Syriha, Antonia; Ptohis, Nikolaos; Skouras, Ioannis; Mainta, Evgenia; Korkolis, Dimitris P.; Machairas, Nikolaos; Sotiropoulos, Georgios C.; Elefsiniotis, Ioannis (Frontiers in Immunology, 2025)
BackgroundThere is a lack in reliable and widely used prognostic scores to predict survival in patients with hepatocellular carcinoma (HCC) receiving immunotherapy. The aim of our study was to develop a prognostic score that could predict 1-year OS in patients with unresectable HCC receiving immunotherapy.MethodsWe studied 100 patients who received 1st line immunotherapy. We did a univariate cox regression analysis to assess which of the patients’ baseline characteristics was associated with OS. Factors strongly associated with OS were used in the multivariate model and their B coefficients were used to produce a normalized score (ALIVE-IO score) that could predict 1-year OS. Internal validation was done using ROC analysis and 10-fold cross-validation. Then, we separated our patients in three risk groups (low, intermediate, high) based on the new score and studied them for their baseline characteristics, response to immunotherapy and OS.ResultsIn univariate analysis, significant correlation with OS was found for ALBI grade (p<0.001, HR=2.725), BCLC stage (p=0.031, HR=1.809), macrovascular invasion (p<0.001, HR=2.587), up-to-7 criteria (p<0.001, HR=0.218) and lymphocyte infiltration (p=0.005, HR=0.485). In the multivariate analysis, three factors were significantly correlated with OS; ALBI grade (grade II vs. I, p=0.025, HR=1.946), up-to-7 criteria (beyond vs. within, p=0.001, HR=3.506) and lymphocyte infiltration (no vs. yes, p=0.016, HR=1.889). The ALIVE-IO score was calculated with the contribution of 1 point for ALBI grade II, 2 points for exceeding up-to-7 criteria and 1 point for absence of lymphocyte infiltration. The score had an AUROC of 0.755 for 1-year OS, with 75% sensitivity and 65.4% specificity. We established three risk groups; low (ALIVE-IO: 0-1), intermediate (ALIVE-IO: 2-3) and high (ALIVE-IO: 4). Objective response was reported in 34.8% of patients in the low risk group, compared to 18.5% in intermediate and 4.3% in high risk patients (p=0.031). The median OS of the three groups was 41, 12 and 3 months, respectively (p<0.001). The 1-year OS was 80%, 41% and 16, respectively.ConclusionThe ALIVE-IO score is a promising tool for predicting 1-year OS in HCC patients undergoing immunotherapy using common laboratory, imaging and histological data frequently used in everyday clinical practice.